(untitled) (Annals of Medical Research, 2023)
Aim: Glioma, particularly glioblastoma (GBM), represents a prevalent and aggressive primary brain tumor with limited curative options. Epileptic seizures often manifest as a common clinical symptom in these patients, but their prognostic significance remains debated. This study aimed to retrospectively analyze the clinical presentations, tumor characteristics, and the impact of seizures on the prognosis of GBM patients. Materials and Methods: A total of 113 adult patients with histologically confirmed GBM treated between April 2018 and January 2022 were included in this retrospective analysis. Data encompassed clinical symptoms, preoperative and postoperative seizures, tumor localization, overall survival (OS), and other relevant factors. Statistical analysis was performed to assess the relationships between seizures and various prognostic parameters. Results: Seizures were present in 39.8% of GBM patients, with 20 patients experiencing both preoperative and postoperative seizures. Preoperative and postoperative seizures were not significantly associated with differences in prognosis (p>0.05). Tumor localization, OS, Karnofsky performance score, and length of hospital stay showed significant differences between patients with and without seizures (p<0.05). Complete resection was achieved in 90.3% of patients, leading to a relatively lower incidence of postoperative seizures. Conclusion: Seizures in GBM patients are associated with OS, Karnofsky performance score, and hospitalization duration, independently of other factors. The presence of seizures serves as a valuable prognostic indicator for GBM, prompting further investigation into its influence on patient outcomes, quality of life, and socioeconomic aspects of survival. These findings emphasize the importance of early seizure management in GBM patients and the need for tailored treatment strategies.